Which technology to investigate visual perception in sport: Video vs. virtual reality - Vignais, N.; Kulpa, R.; Brault, S.; Presse, D.; Bideau, B. (Human Movement Science, 2015)
Visual information uptake is a fundamental element of sports involving interceptive tasks. Several methodologies, like video and methods based on virtual environments, are currently employed to analyze visual perception during sport situations. Both techniques have advantages and drawbacks. The goal of this study is to determine which of these technologies may be preferentially used to analyze visual information uptake during a sport situation. To this aim, we compared a handball goalkeeper`s performance using two standardized methodologies: video clip and virtual environment. We examined this performance for two response tasks: an uncoupled task (goalkeepers show where the ball ends) and a coupled task (goalkeepers try to intercept the virtual ball). Variables investigated in this study were percentage of correct zones, percentage of correct responses, radial error and response time. The results showed that handball goalkeepers were more effective, more accurate and started to intercept earlier when facing a virtual handball thrower than when facing the video clip. These findings suggested that the analysis of visual information uptake for handball goalkeepers was better performed by using a `virtual reality`-based methodology. Technical and methodological aspects of these findings are discussed further.